Soluble programmed death-ligand 1 (sPDL1) and neutrophil-to-lymphocyte ratio (NLR) predicts survival in advanced biliary tract cancer patients treated with palliative chemotherapy - Ha, Hyerim; Nam, Ah-Rong; Bang, Ju-Hee; Park, Ji-Eun; Kim, Tae-Yong; Lee, Kyung-Hun; Han, Sae-Won; Im, Seock-Ah; Kim, Tae-You; Bang, Yung-Jue; Oh, Do-Youn (Oncotarget, 2016)
Programmed death-ligand 1 (PD-L1) expression in tumor tissue is under investigation as a candidate biomarker in immuno-oncology dug development. The soluble form of PD-L1 (sPDL1) is suggested to have immunosuppressive activity. In this study, we measured the serum level of sPDL1 and evaluated its prognostic implication in biliary tract cancer (BTC). Blood was collected from 158 advanced BTC patients (68 intrahepatic cholangiocarcinoma, 56 gallbladder cancer, 22 extrahepatic cholangiocarcinoma and 12 ampulla of vater cancer) before initiation of palliative chemotherapy. Serum sPDL1 was measured using an enzyme-linked immunosorbent assay. Clinical data included neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and systemic immune-inflammation index (SII, neutrophil × platelet/lymphocyte). The patients were assigned to two cohorts (training and validation cohort) using a simple random sampling method to validate the cut-off value of each marker. Validation was performed using a twofold cross-validation method. Overall survival (OS) of all patients was 9.07 months (95% CI: 8.20-11.33). Median sPDL1 was 1.20 ng/mL (range 0.03-7.28, mean 1.50, SD 1.22). Median NLR, PLR and SII were 2.60, 142.85 and 584.93, respectively. Patients with high sPDL1 (≥0.94 ng/mL) showed worse OS than patients with low sPDL1 (7.93 vs. 14.10 months, HR 1.891 (1.35-2.65), p<0.001). In multivariate analysis, high sPDL1 and NLR were independent poor prognostic factors. In conclusion, serum sPDL1 can be measured and has significant role on the prognosis of advanced BTC patients treated with palliative chemotherapy.